The sovereign individual - Davidson, James Dale (Simon & Schuster, 1997)
The computer revolution, in the authors' dire scenario, will subvert and destroy the nation-state as globalized cybercommerce, lubricated by cybercurrency, drastically limits governments' powers to tax. They further predict that the next millennium will see an enormous decline in the influence of politicians, lobbyists, labor unions and regulated professions as new information technologies democratize talent and innovation and decentralize the workplace. In their forecast, citizenship will become obsolete; new forms of sovereignty reminiscent of medieval merchant republics will spring up; electronic plebiscites will decide legislative proposals; mafias, renegade covert agencies and criminal gangs will exercise much more behind-the-scenes power. Davidson and Rees-Mogg, who publish Strategic Investment, a financial newsletter, present an apocalyptic exercise that is unconvincing. Appendices offer advice to "Sovereign Individuals" (members of the information elite) on how to invest, find tax shelters, avoid criminals and list one's business on the World Wide Web.